Methodological appproach to the development of SAQ movement skills in basketball - Trunic, N.; Mladenovic. M. (Sport Science & Practice, 2015)
This paper explains the significance of the development of SAQ skills for young basketball players. Apart from this, the paper offers an overview of characteristics of training, main principles and methodological notes for the triangle training of speed, agility and quickness. The tendencies of anthropological development of children are completely compatible with the goals of developing SAQ skills, which is proved by the overview of sensitive periods of development and principles which refer to the long-term programme of their implementation in the training technology. The verification of the significance of the development of these characteristics for young basketball players has also been highlighted, as the basis for qualitative fitness, technical, tactical and situational detection in the years when the highest sports achievements are expected. Therefore, an overview of the main characteristics of the training of speed, agility and quickness has been given as an example of optimal training of young basketball players.